Profiling the dynamics of the active transcriptome in the juvenile and adult brain using spatial transcriptomics - Mishi, Ruvimbo (Department of Human Biology, 2024)
The human brain is made up of a collection of distinct cell types that play specialized roles in maintaining proper brain function. The process of maturation of this complex organ can be assessed by examining the dynamics of gene expression within the various cell types. Previous studies have used single-cell/single nucleus RNA-sequencing (sc/snRNA-seq) to provide vital information on gene expression at a cell-specific level. These studies, which focused on either the pre-natal or adult brain, lacked comprehensive information about the spatial dynamics of cell type-specific gene expression over the course of brain maturation. This information is important for understanding the dynamics of gene expression in the context of changing tissue architecture over the course of maturation. This study aims to contribute to our understanding of the maturing human brain by obtaining the spatial gene expression information of the antemortem brain as it matures from postnatal to adult state. Samples from the human temporal cortex (4-, 15- (x2), and 31-year-old) were obtained during elective surgeries to treat epilepsy. Tissue samples were freshly frozen in OCT. H&E (hematoxylin and eosin) staining was employed for the initial screening of the tissue samples. The 10x Genomics Visium Spatial gene expression system was used to obtain genome-wide spatial gene expression patterns. The Visium FASTQ files were aligned to the human transcriptome using 10X Genomics SpaceRanger. To spatially map the brain cell types, the Visium data was integrated with snRNAseq data using the cell2location method. In situ hybridization chain reaction was used to validate the identified gene expression patterns. Fifty-four cell types, annotated using the current published human temporal lobe cell atlas, were spatially mapped by integrating Visium spatial gene expression and existing snRNA-seq datasets from the same samples. Moreover, this integrative analysis revealed potential changes in the distribution of cell types during brain maturation, highlighting the importance of studying the spatiotemporal dynamics of cell types to better understand brain development and function. Previously identified layer-enriched genes were confirmed to be present in all the samples. Furthermore, layer-enriched genes that showed an increase in expression during brain maturation were identified. The findings of this study contribute to the human brain cell atlas through the provision of spatial gene expression information in the maturing temporal cortex.